Job Creation in Mozambique : Is Labor Law Reform the Answer? - Ministry of Planning and Development, Mozambique (World Bank, Washington, DC, 2013)
This paper analyzes the potential economic impact of changes to the labor laws proposed in 2006. The economic logic behind these reforms is reviewed, and the conditions under which the reforms could be expected to have the maximum impact on employment are isolated. Next, the experiences of selected developing countries which have undertaken similar reforms are reviewed, which showed the importance of initial conditions and economic trends outside of the labor market in ensuring a successful reform. Third, the main provisions of the proposed reforms are explained. The analysis concludes that given Mozambique s initial conditions, including strong demand from private sector employers for change, the scope of proposed reforms, and the potential for continued economic growth, the reforms should increase firms' profit margins, and as a result, a positive employment effect is possible in the medium term. The analysis also shows that although the reforms are deep compared with the starting point, even if reforms are enacted, Mozambique's labor market would still be classified as rigid by international benchmarks. The report concludes with a discussion of the possible social and poverty effect. In the short run, there is a danger of layoffs in some of the larger firms which had previously reported being overstaffed. If this happens, the poverty effect would certainly be negative in the short run. The concluding section notes that other countries have avoided these types of layoffs by introducing transition arrangements.